2014
DOI: 10.1016/j.actbio.2014.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Novel osteoinductive photo-cross-linkable chitosan-lactide-fibrinogen hydrogels enhance bone regeneration in critical size segmental bone defects

Abstract: The purpose of this study was to develop and characterize a novel photo-cross-linkable chitosan-lactide-fibrinogen (CLF) hydrogel and evaluate the efficacy of bone morphogenetic protein-2 (BMP-2) containing CLF hydrogel for osteogenesis in vitro and in vivo. We synthesized the CLF hydrogels and characterized their chemical structure, degradation rate, compressive modulus, and in vitro BMP-2 release kinetics. We evaluated bioactivities of the BMP-2 containing CLF hydrogels (0, 50, 100, and 500 ng/ml) in vitro u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 48 publications
1
36
1
Order By: Relevance
“…Cytotoxicity and cell viability suggest that GDF-5loaded HA hydrogel has proper biocompatibility for use as a scaffold which can induce osteogenesis. Moreover, the HA hydrogel showed improved osteogenesis in both in-vitro tests, the results from these tests show that the HA hydrogel can be used as a scaffold for bone tissue regeneration [149]. Gelatin hydrogels were also used for bone regeneration at both the critical-sized bone defect.…”
Section: Journal Of Biomedical Sciences Issn 2254-609xmentioning
confidence: 93%
“…Cytotoxicity and cell viability suggest that GDF-5loaded HA hydrogel has proper biocompatibility for use as a scaffold which can induce osteogenesis. Moreover, the HA hydrogel showed improved osteogenesis in both in-vitro tests, the results from these tests show that the HA hydrogel can be used as a scaffold for bone tissue regeneration [149]. Gelatin hydrogels were also used for bone regeneration at both the critical-sized bone defect.…”
Section: Journal Of Biomedical Sciences Issn 2254-609xmentioning
confidence: 93%
“…In vitro and in vivo studies demonstrated the ability of the hydrogel to deliver nucleic acid to the surrounding tissues and cells leading to effective blocking of TNF-α [99]. Recently, Kim et al developed a photocrosslinked hydrogel made of chitosan-lactide-fibrinogen (CLF) as a delivery system for BMP-2 [100]. Chitosan and lactide in the hydrogel controlled the physiochemical properties of the hydrogel [101].…”
Section: Orthopedic Regenerative Engineeringmentioning
confidence: 96%
“…The results indicated increased cell viability, neo-osteogenesis, and bone healing. The responses were dependent on the dose of the growth factor [100]. …”
Section: Orthopedic Regenerative Engineeringmentioning
confidence: 99%
“…The use of β-tri-calcium phosphate that is more soluble than hydroxyapatite (Yamada et al, 1997) and chitosan, a lysozyme-biodegradable biopolymer (New et al, 2009), makes the CS-CP composite susceptible for bioresorption and biodegradation. Moreover, CS composites have been demonstrated osteoinductive effects (Jebahi et al, 2013;Kim et al, 2014;Kung et al, 2011) in vitro and in vivo. Thus, the CS-CP composites herein prepared are potentially biodegradable and osteoinductive, and demonstrated adequate porosity and mechanical properties for treating bone defects.…”
Section: Discussionmentioning
confidence: 99%